(untitled) (World Bulletin of Social Sciences, 2023)
In the article, how to teach a second language, the stages of students’ acquisition of a second language, and the linguo-cultural approach in teaching Uzbek as a second language in the general secondary education system, or clearly defined tasks for teaching culture. The reasons for choosing the appropriate methodology and the six required teaching technologies are presented.